The Great Masquerade: A Rare Presentation of Spinal Tuberculoma - Arnesh Bhattacharya (JCDR Research and Publications Private Limited, 2021)
Spinal tuberculomas form a meagre fraction of cases of Tuberculosis (TB). Most common presentation of spinal tuberculoma is weakness. A 45-year-old female presented with dysthesias, gait instability and numbness involving both lower limbs for a period of 7-10 days. Patient was vitally stable (blood pressure of 128/78 mm of Hg, pulse rate of 86 beats per minute and respiratory rate of 18 breaths per minute with a normal pattern), alert and co-operative. Neurological examination suggested non length dependant sensory involvement of lower limbs, sensory ataxia and areflexia, level of lesion being at the Dorsal Root Ganglia (DRG) (sensory neuronopathy). Contrast Enhanced Magnetic Resonance Imaging (CEMRI) spine revealed tuberculoma at D9 spinal level. Patient responded to Antitubercular Therapy (ATT) and recovered. The intention of sharing the clinical experience is with the sole purpose of remembering the fact that common pathologies may at times be great mimickers. In the present case, while a lot of rare causes (autoimmune, neoplastic) were searched for, tuberculoma happened to be the culprit.